Association between Workplace Harassment and Job Satisfaction in Nepalese Commercial Banks - Aryal, Arshiya; Bunchapattanasakda, Chanchai (Nepalese Journal of Management Science and Research, 2019)
Workplace harassment is a common issue in the present context. It can cause severe effects on an employee’s life, family, and career. The study examined workplace harassment and its effect on job satisfaction in the banking sector of Nepal. The evidences confirm that Verbal harassment, Physical harassment, and Mental harassment have negative and significant impact on Job satisfaction. It further confirms that Verbal harassment, Physical harassment, and Mental harassment have positive and significant impact among themselves. Such harassments have affected the assistant and junior level officers resulting to low job satisfaction at their workplace.